Incidence and directions of educational migration of Tuvan youth - Chernyshev, Konstantin A.; Mitiagina, Ekaterina V.; Chernysheva, Natalia V.; Petrov, Evgeniy Yu. (The New Research of Tuva, 2023)
The article examines the internal migration of young Tuvans within Russia, which is attributed to acquiring higher education. It is noted that interregional educational migration is predominantly recurrent. We have studied the directions of migration flows using non-traditional sources of information. One of them comprises digital traces of 3,090 VK users who indicated locations in the Republic as their birthplaces or settlements where they had finished school. In addition, we use the data provided by the Ministry of Education of the Republic of Tuva on the places where 1,282 students were obtaining higher education in the 2021/2022 academic year (admissions in 2016–2021) within the framework of the purpose-oriented program for training human resources.Tuvan State University is located in the capital of the region and turns out to be the most popular university among the residents of the Republic. The significance of Kyzyl as a center of higher education is similar to those of the capital cities of the neighboring Altai Republic and the Republic of Khakassia in terms of organizing intraregional migration.Siberian regions (Krasnoyarsk Krai, Novosibirsk and Tomsk Oblasts) as well as Moscow are considered to be the main directions of the interregional migration flows. Comparing the two sources of information on educational migration provides a more accurate picture. The geographies of students’ migration from Tuva, identified on the basis of their digital footprints, are characterized by a greater diversity in comparison with those of the students involved in the targeted training program.The current distribution is influenced by territorial accessibility of HEIs in other subjects of the Russian Federation, the lower level of socio-economic development of Tuva compared to most Russian regions and a limited number of higher education institutions in the Republic.
Keywords: Republic of Tuva; internal migration; educational migration; youth migration; Kyzyl; population of Tuva; digital footprints; social networks